Performance of nursing in geriatrics: main care and procedures (Research, Society and Development, 2022)
Mainly for the elderly, nursing conveys personal care that prevents, reduces or manages the consequences and vulnerabilities resulting from the aging process. It is known that aging is inevitable and, according to WHO data, in the coming decades the world population over 60 years will increase from 841 million to 2 billion by 2050. The present work aims to report the main care and procedures and the performance of nursing in geriatrics. We searched the VHL for articles published and indexed in the LILACS, MEDLINE AND SCIELO databases, from 2017 to 2022, in English, Spanish and Portuguese. After pre-established criteria, 24 articles were selected. The main functions of gerontological nursing are: taking care of the health of the elderly; assist the elderly when they are sick; guide the elderly to prevent health problems; assist and care for the elderly in recovery and rehabilitation; assist the elderly on a continuous basis, in cases of chronic disease and at the end of life; in addition to performing a thorough examination of the patient, which includes assessments of the family and the community in which the elderly person is hospitalized. Through these various assessments, a system of care and personal assistance is developed to fully assist the patient, in hospital facilities, in residences, nursing homes or in other areas of residence of the elderly. The monitoring and care of the nursing service in relation to the elderly is very important, as the physical and personal care provided by the nurse favors comfort conditions for the elderly, leading to well-being.